A Broad Survey of Gene Body and Repeat Methylation in Cnidaria Reveals a Complex Evolutionary History. (1st February 2022) - Zhang, Xinhui; Jacobs, David
Abstract: DNA methylation, an important component of eukaryotic epigenetics, varies in pattern and function across Metazoa. Notably, bilaterian vertebrates and invertebrates differ dramatically in gene body methylation (GbM). Using the frequency of cytosine-phospho-guanines (CpGs), which are lost through mutation when methylated, we report the first broad survey of DNA methylation in Cnidaria, the ancient sister group to Bilateria. We find that: 1) GbM differentially relates to expression categories as it does in most bilaterian invertebrates, but distributions of GbM are less discretely bimodal. 2) Cnidarians generally have lower CpG frequencies on gene bodies than bilaterian invertebrates potentially suggesting a compensatory mechanism to replace CpG lost to mutation in Bilateria that is lacking in Cnidaria. 3) GbM patterns show some consistency within taxonomic groups such as the Scleractinian corals; however, GbM patterns variation across a range of taxonomic ranks in Cnidaria suggests active evolutionary change in GbM within Cnidaria. 4) Some but not all GbM variation is associated with life history change and genome expansion, whereas GbM loss is evident in endoparasitic cnidarians. 5) Cnidarian repetitive elements are less methylated than gene bodies, and methylation of both correlate with genome repeat content. 6) These observations reinforce claims that GbM evolved in stem Metazoa. Thus, this work supports overlap between DNA methylation processes in Cnidaria and Bilateria, provides a framework to compare methylation within and between Cnidaria and Bilateria, and demonstrates the previously unknown rapid evolution of cnidarian methylation.